Rapidly Growing, High-Risk Gastrointestinal Stromal Tumor of the Stomach: A Case Report - Sung Jin Lim; Han Mo Yoo; Seung-Woo Lee; Hae Joung Sul; Dong Soo Lee (Yong Chan Lee, 2023)
An increase in the volume of endoscopic procedures performed in recent times has led to increasing detection rates of asymptomatic gastrointestinal subepithelial tumors. However, accurate diagnosis and risk assessment of these tumors preoperatively is challenging. A 70-year-old man patient visited the emergency department for evaluation of melena. Emergency endoscopy revealed an ulcerated subepithelial tumor (8 cm in size) in the gastric cardia and fundus. Computed tomography and upper endoscopy performed at another hospital 6 months earlier were reviewed; the mass showed a significant increase in size (from 2 cm to 8 cm). The patient underwent surgical resection of the mass and was diagnosed with a high-risk gastrointestinal stromal tumor (GIST). In this article, we describe a rare case of a rapidly growing GIST at a rate significantly greater than commonly reported rates.